Adverse Environmental Impact: 30-Year Search for a Definition - David A. Mayhew; Paul H. Muessig; Loren D. Jensen (The Scientific World Journal)
Since passage of the Clean Water Act in 1972, there has been a long, unresolved struggle to define a key phrase in Section 316(b) of the act: “adverse environmental impact” (AEI). Section 316(b) requires that the best technology available be used in cooling-water intake structures to minimize AEI due to entrainment and impingement of aquatic organisms. Various attempts were made to evaluate and define AEI, including focused national conferences on impact assessment. Unresolved arguments regarding AEI were reinvigorated following the 1995 Consent Decree requiring EPA to propose new rules to implement Section 316(b). This article reviews and compares eight proposed definitions of AEI. Six of the definitions define AEI as impact expressed at the population or higher level of biological organization. The two remaining definitions are unrelated to populations: a 1% cropping of the near-field organisms and “one fish equals AEI”. The latter definition is based on the desire of some stakeholders to define AEI as the loss of any public trust resources. Equating loss of public trust resources with AEI hampers consensus on a definition because a societal-based policy concept (public trust resources) is commingled with science-based definitions based on population effects. We recommend that a population-based definition of AEI be incorporated into Section 316(b) guidance and observe that this will not preclude a state from exercising its law and policy to protect public trust resources.